Financial Statement Analysis to Assess Corporate Resilience in Facing Global Economic Crises - Hardiyanti, Siti Epa (PT Larva Wijaya Penerbit, 2025)
This study explores the application of financial statement analysis to evaluate corporate resilience during global economic crises. The research focuses on identifying key financial indicators that influence a firm's ability to endure and recover from external economic shocks. Utilizing data from companies across five strategic sectors, the study develops a composite Resilience Index incorporating liquidity, solvency, profitability, and efficiency ratios. The findings reveal that firms with strong cash flows, low leverage, and high liquidity exhibit superior crisis performance and faster post-crisis recovery. The study contributes to the existing literature by proposing an integrated resilience assessment framework and provides practical insights for managers, investors, and policymakers in enhancing financial preparedness.